A Journey with Elie Metchnikoff: From Innate Cell Mechanisms in Infectious Diseases to Quantum Biology - Merien, Fabrice (Frontiers in Public Health, 2016)
Many reviews of Elie Metchnikoff’s work have been published, all unanimously acknowledging the significant contributions of his cellular theory to the fields of immunology and infectious diseases. In 1883, he published a key paper describing phagocytic cells in frogs. His descriptions were not just about phagocytes involved in host defense, he also described how these specialized cells eliminated degenerating or dying cells of the host. This perspective focuses on key concepts developed by Metchnikoff by presenting relevant excerpts of his 1883 paper and matching these concepts with challenges of modern immunology. A new approach to macrophage polarization is included to introduce some creative thinking about the exciting emerging area of quantum biology.